Global Capabilities Framework for Public Relations and Communication Management - Australia - Sison, M.; Wolf, Katharina (RMIT / Curtin University, 2018)
The Global Capabilities Framework-Australia study was undertaken between March 2017 and January 2018. The threestage research project, which included a Delphi study, an online survey and focus group discussions, involved public relations and communication practitioners, employers and educators from around the country. The study resulted in a list of ten core capabilities for public relations and communication management.